Rare Earth Element Determination in Olivine by Laser Ablation-Quadrupole-ICP-MS: An Analytical Strategy and Applications - Kamber, Balz; Tomlinson, Emma (My University, 2017)
Olivine offers huge, largely untapped, potential for improving our understanding of magmatic and metasomatic processes. In particular, a wealth of information is contained in rare earth element (REE) mass fractions, which are well studied in other minerals. However, REE data for olivine are scarce, reflecting the difficulty associated with determining mass fractions in the low ng g−1 range and with controlling the effects of LREE contamination. We report an analytical procedure for measuring REEs in olivine using laser ablation quadrupole‐ICP‐MS that achieved limits of determination (LOD) at sub‐ng g−1 levels and biases of ~ 5–10%. Empirical partition coefficients (D values) calculated using the new olivine compositions agree with experimental values, indicating that the measured REEs are structurally bound in the olivine crystal lattice, rather than residing in micro‐inclusions. We conducted an initial survey of REE contents of olivine from mantle, metamorphic, magmatic and meteorite samples. REE mass fractions vary from 0.1 to double‐digit ng g−1 levels. Heavy REEs vary from low mass fractions in meteoritic samples, through variably enriched peridotitic olivine to high mass fractions in magmatic olivines, with fayalitic olivines showing the highest levels. The variable enrichment in HREEs demonstrates that olivine REE patterns have petrological utility.
PUBLISHED
Keywords: Laser ablation; Quadrupole-ICP-MS; Olivine; Rare earth elements; Partitioning; In situ analysis